The case of LVMH and BVLGARI : mergers & acquisitions - Farinha, Tânia Rafaela da Silva (2014)
LVMH Moët Hennessy - Louis Vuitton, the biggest player on the luxury industry, has announced on March 2011 a further step on its consolidation strategy. LVMH announced the acquisition of Bulgari, a company owned majorly by the Bulgari family. This thesis aims to analyse the value creation potential of this acquisition. The data of the valuation exercise is prior to the acquisition, aiming to understand the deal from an ex-ante point of view. The valuation exercise is based on the valuation literature and on the analysis of the luxury industry players, structure, profitability and expected growth. Bulgari, pre-deal, is considered to be overvalued. The company is failing to keep up with the high growth rate of the luxury industry. The synergies are estimated at 96% of the company’s pre-deal estimated price and around 60% of its market capitalization.